Antithrombotic Therapy for DVT/PE - Hyers, Thomas M. (Hämostaseologie, 1997)
Problems with unfractionated heparin as an antithrombotic have led to the development of new therapeutic agents. Of these, low molecular weight heparin shows great promise and has led to out-patient therapy of DVT/PE in selected patients. Oral anticoagulants remain the choice for long-term therapy. More cost-effective ways to give oral anticoagulants are needed.
Keywords: Heparin; low molecular weight heparin (LMWH); oral anticoagulants; venous thromboembolism